Between mutiny and obedience the case of the French Fifth Infantry Division during World War I - Smith, Leonard V. 1957- (Princeton Univ. Press, 1994)
The division established a distinguished fighting record from 1914 to 1916, yet proved in 1917 the most mutinous division in the entire French army, only to regain its elite reputation in 1918. Drawing on sources from ordinary soldiers to well-known commanders such as General Charles Mangin, the author explains how the mutinies of 1917 became an explicit manifestation of an implicit struggle that took place within the French army over the whole course of the war